107 A MULTIDISCIPLINARY NETWORK OF SOCIAL SUPPORT CAN POSITIVELY AFFECT OUTCOME IN LOWER SOCIOECONOMIC PATIENTS (MEDICAL/MEDICAID INSURANCE) AFTER HEART TRANSPLANTATION. (10th December 2015) - Seid, A.; Kobashigawa, J. A.; Patel, J. K.; Yamada, B.; Hamilton, M.
Abstract : Background: Lower socio-economic status (SES) has been reported to have a significant adverse impact on post-heart transplant outcomes. Lower SES patients qualify for government supported health care including MediCal and Medicaid. It has also been demonstrated that heart transplant patients with these forms of health insurance at the time of transplant have subsequent lower survival, which may be due to inadequate social support, lack of understanding medication instructions and poor follow-up compliance. A heart transplant program with a committed team to offer support such as a dedicated social worker, outpatient housing, and patient mentoring could change outcome of lower SES patients. In our heart transplant program, we have such social support. Methods: We reviewed 261 patients transplanted between 7/97 and 9/01 and determined type of insurance at time of transplant. Of those patients 239 had insurance data available. Survival and the development of cardiac allograft vasculopathy (CAV) defined as angiographic lesions ≥30% stenosis was determined. Patients were divided into 3 insurance groups: 1) Private insurance, 2) Medicare and 3) MediCal/Medicaid. Results: Gender, ischemic time, donor age, and donor gender were similar among the three groups. Significantly fewer Caucasian patients were seen in the MediCal/Medicaid Group (50% vs. Private: 71%, Medicare: 81%) p≤0.001. The patients in the MediCal/Medicaid Group were younger at time of transplant than the other groups: MediCal/Medicaid Group mean age 45 years vs. Private 54 years vs. Medicare 61 years, p≤0.001. There was no difference in survival between patients with private insurance, Medicare or MediCal/Medicaid at 36 months (76% vs. 79% vs. 73% respectively; p=0.86). There was also no significant difference in freedom from the development of CAV between the three groups over the same period of time (75% vs. 79% vs. 82% respectively; p=0.76). Conclusion: Lower socio-economic (MediCal/Medicaid insurance) heart transplant patients appear to have comparable outcome to other patients after heart transplant when supported by a dedicated social worker in a highly integrated multi-disciplinary transplant program.